Managing employment dismissals in Malaysia and England – a legal guide - Lee, Sook Ling; Guru Dhillon (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper explains the essential steps that will be taken by the workman when he/she is dismissed. Subsequently, this paper highlights and explains pertinent matters that will be addressed in the Industrial Court. These include, among others, the burden of proof for dismissal cases in Industrial Court, the alternative remedies that can be offered to the claimant and the requirement of the mitigation of damages. A comparative analysis with England has been conducted to assess whether the current practice in managing employment dismissals in Malaysia is up to date and on par with international standards and expectations. The materials and data have been compiled from Malaysian and English legislations, case laws, journal articles, related official websites, and online databases. This paper is intended to benefit businesses or human resource managers, legal practitioners, law academics, law students, workmen, and employers.